Multimode Magneto-Optical Fiber Based on Borogermanate Glass Containing Tb3+ for Sensing Applications - Franco, Douglas F. [UNESP]; Morency, Steeve; Messaddeq, Younès [UNESP]; Nalin, Marcelo [UNESP] (MDPI, 2025)
A multimode magneto-optical fiber based on Tb3+-containing borogermanate glass was designed, fabricated, and characterized, aiming at potential sensing applications. There are continuing challenges in the development of single-mode (SMF) or multimode (MMF) optical fibers doped with rare-earth (RE) ions and exhibiting high Verdet constants, related to devitrification of the precursor glass. Most RE-doped glass compositions are not suitable as precursors for core-cladding fiber production due to devitrification processes and consequent poor optical quality. Application as Faraday rotators is limited by the intrinsically low Verdet constant of silica (~0.589 rad T-1 m-1 at 1550 nm and 0.876 rad T-1 m-1 at 1310 nm). Borogermanate glasses are good candidates for manufacturing optical fibers due to their excellent potential to solubilize high concentrations of Tb3+ ions as well as satisfactory thermal stability. In this work, a magneto-optical core-cladding borogermanate fiber with a 227 μm diameter was fabricated, with characterization using differential scanning calorimetry (DSC), thermomechanical analysis (TMA), viscosity measurements, M-lines spectroscopy, UV-Vis-NIR absorption spectroscopy, the cut-back technique, and magneto-optical measurements. The measured numerical aperture (NA) was 0.183, with minimum attenuation of 13 dB m-1 at 1270 nm. The Verdet constant (VB) reached -6.74 rad T-1 m-1 at 1330 nm.